Increased Factor VIII Complex in Fulminant Hepatic Failure - Langley, P G; Hughes, R D; Williams, Roger (Thrombosis and Haemostasis, 1985)
In 30 patients with fulminant hepatic failure (FHF) all three components of the factor VIII complex were significantly increased (VIIIC = 6.43 ± 1.12 u/ml; VIIIRAg = 3.91 ± 0.25 u/ ml; VIIIvWF = 3.89 ± 0.29 u/ml). There was good correlation between all three parameters in control subjects, but only between VIIIRAg and VIIIvWF (r= 0.67; p <0.001) in patients with FHF. VIIIC was significantly higher than VIIIRAg and VIIIvWF. These results suggest that VIIIC and VIIIRAg are increased by different mechanisms in FHF. These processes may include endothelial cell damage, reduced reticuloendothelial system function and lack of production of inactivating substances by the damaged liver.Platelet adhesion to glass beads was increased in FHF (36.4 ± 5.9% compared to 16.6 ± 2.1%, p <0.01). There was no significant correlation between platelet adhesion and any of the parameters of the factor VIII complex. Thus the increase in platelet adhesion cannot be due to the increase in VIIIvWF in FHF.
Keywords: Factor VIII; fulminant hepatic failure